أثر استخدام استراتيجية التعلم باللعب لترقية فاعلية التلاميذ في مهارة الكلام بمدرسة الفتاح الابتدائية الأهلية بمدينة باتو - Kurniawan, M. Andi; Sulaila, Neneng; Al Anshory, Abdul Muntaqim; Mubaligh, Ahmad (Jurusan Pendidikan Bahasa Arab, 2023)
The strategy of learning by playing is considered an integral part of the process of mental growth and intelligence, due to the importance of games. Many educational institutions have attached great importance to games in their curricula, and they are an educational means for developing speaking skill. This research aims to find out the effect of using the learning-by-play strategy to improve students' effectiveness in speaking skill. This research is a descriptive experimental research. The results of the research were obtained and analyzed using the method of observation for Arabic language teachers and direct interview. In analyzing the data, the researcher followed the method of Mills and Huberman, which is collecting, presenting and discussing data. The researcher reached the results of the research, including: (1) that the use of the learning strategy by playing has a positive effect to improve students' effectiveness in speaking skill. (2) The students interact in the study through learning through playing, and this is apparent from the result of observing the students’ learning activities with a score of 92.5% (what do you say game) and 95% (the picture description game), which indicates that it occurred between 81-100%, which means excellent.